PERBEDAAN MODEL PEMBELAJARAN INKUIRI TERBIMBING DAN DIRECT INSTRUCTION TERHADAP AKTIVITAS DAN HASIL BELAJAR MAHASISWA UNIVERSITAS QUALITY - Dedi Holden Simbolon (JURNAL CURERE, 2020)
This studied aims to analyze the differences between student learning outcomes taught by using the guided inquiry compared to the Direct Instruction learning models. This research is quasi-experimental. The study population was students of Quality University of Medan in semester V of the odd school year 2019/2020. The sampling technique was using cluster random sampling consisting of two classes with a total sample of 67 people. From the research results obtained, it can be concluded that there are differences in the Guided Inquiry learning model and the Direct Instruction model in improving the learning outcomes of student research methodologies. Where classes taught using the guided inquiry learning model have higher learning outcomes compared to classes taught using the direct learning model (Direct Instruction).